The Significance of the Sulfatase Pathway for Local Estrogen Formation in Endometrial Cancer - Sinreih, Maša; Knific, Tamara; Anko, Maja; Hevir, Neli; Vouk, Katja; Jerin, Aleš; Frković Grazio, Snježana; Rižner, Tea Lanišnik (Frontiers in Pharmacology, 2017)
Endometrial cancer is the most common estrogen-dependent gynecological malignancy in the developed World. To investigate the local formation of estradiol (E2), we first measured the concentrations of the steroid precursor androstenedione (A-dione) and the most potent estrogen, E2, and we evaluated the metabolism of A-dione, estrone-sulfate (E1-S), and estrone (E1) in cancerous and adjacent control endometrium. Furthermore, we studied expression of the key genes for estradiol formation via the aromatase and sulfatase pathways. A-dione and E2 were detected in cancerous and adjacent control endometrium. In cancerous endometrium, A-dione was metabolized to testosterone, and no E2 was formed. Both, E1-S and E1 were metabolized to E2, with increased levels of E2 seen in cancerous tissue. There was no significant difference in expression of the key genes of the aromatase (CYP19A1) and the sulfatase (STS, HSD17B1, HSD17B2) pathways in cancerous endometrium compared to adjacent control tissue. The mRNA levels of CYP19A1 and HSD17B1 were low, and HSD17B14, which promotes inactivation of E2, was significantly down-regulated in cancerous endometrium, especially in patients with lymphovascular invasion. At the protein level, there were no differences in the levels of STS and HSD17B2 between cancerous and adjacent control tissue by Western blotting, and immunohistochemistry revealed intense staining for STS and HSD17B2, and weak staining for SULT1E1 and HSD17B1 in cancerous tissue. Our data demonstrate that in cancerous endometrium, E2 is formed from E1-S via the sulfatase pathway, and not from A-dione via the aromatase pathway.